Three new species of Quedius elpenor group (Coleoptera: Staphylinidae: Staphylinini: Quediina) from China - Cai, Yan-Peng; Zhou, Hong-Zhang (Zootaxa, 2015)
Three new species of the subgenus Distichalius Casey, 1915 of the genus Quedius Stephens, 1829 are described based on specimens collected in China: Q. (Distichalius) biprominulus sp. nov., Yunnan; Q. (Distichalius) fusus sp. nov., Beijing; and Q. (Distichalius) paululus sp. nov., Sichuan. The new species belong to the Quedius elpenor group and increase the number of species of this group to 10. Line drawings and color illustrations of adults and genitalia of the new species are given. A key to all species of this group is provided and their geographical distribution is mapped.